1998
DOI: 10.1007/s001070050268
|View full text |Cite
|
Sign up to set email alerts
|

Zum Recycling von Span- und MDF-Platten

Abstract: Teil 1: Uber die Hydrolyseresistenz yon ausgehiirteten Harnstoff-Formaldehydharzen (UF-Harzen) in Span-und mitteldichten Faserplatten (MDF) R. Franke, E. RoffaelDas Recycling yon Holzwerkstoffen hat in den letzten Jahren in Deutschland durch eine zunehmend strenger werdende Gesetzgebung immer mehr an Bedeutung gewonnen. Derzeit scheinen Verfahren, die auf dem Prinzip der Hydrolyse durch Dampfbehandlung basieren, das Interesse der Industrie zu wecken. In diesem Zusammenhang wird in dieser Arbeit untersucht, wie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The high pH of the MDF samples likely originates from ammonium hydroxide, which is converted from ammonia in watery solutions. The ammonia, in turn, is hydrolytically cleaved from the UF-resin polymers [18,19]. For all samples, the amount of formic and acetic acid rises with increasing severity.…”
Section: Influence Of the Severity On The Hydrolysis Reactions Of Thementioning
confidence: 95%
See 1 more Smart Citation
“…The high pH of the MDF samples likely originates from ammonium hydroxide, which is converted from ammonia in watery solutions. The ammonia, in turn, is hydrolytically cleaved from the UF-resin polymers [18,19]. For all samples, the amount of formic and acetic acid rises with increasing severity.…”
Section: Influence Of the Severity On The Hydrolysis Reactions Of Thementioning
confidence: 95%
“…While the highest removal rate of cured resins can be achieved using acidic solutions [16], it is still possible to remove up to two-thirds of cured resin using only water at temperatures below 100 • C [17]. More intense reaction conditions, as they are found in steam treatments, can further improve the resin hydrolysis [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Wan et al [13] mentioned that there have been developed several methods for reconstituting the waste from PBs and other medium density fiberboards (MDF) in order to solve the problem of recycling the wood composites. The processing can be chemically thermomechanical [14,15], hydrothermal [16][17][18], chemical [19] or mechanical [20][21][22][23][24]. According to Wan et al [13], it was confirmed by research results that common types of urea-formaldehyde (UF) 2 of 16 and phenol-formaldehyde (PF) resins are suitable for manufacturing PBs and MDF from recycled wood materials using conventional technology.…”
Section: Introductionmentioning
confidence: 99%
“…Fractionation is a necessary step to enable a material recycling of waste MDF. Using hydrothermal or steam-based treatments it is possible to hydrolyze the urea-formaldehyde (UF) based resins [10][11][12][13][14], which make up the majority of the resins used in MDF production [15]. To compare chemical and structural changes in differing steam-based treatments of lignocellulosic material, the severity factor, which combines the two main process parameters treatment duration and temperature, can be used [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The liquid fraction contains solubilized carbohydrates and lignin as well as a high amount of nitrogen and acids (acetic and formic). The pH of the liquid extract of around 8 is high in comparison to liquid fractions of steam treated native lignocellulosic material, due to a high amount of ammonium hydroxide following the degradation of the urea-formaldehyde resins [12,13]. As the fiber fraction accounts for the major fraction after the steam refining treatment, the development of an economically viable recycling pathway for the fibers is of prime interest for the advancement of material recycling of waste MDF.…”
Section: Introductionmentioning
confidence: 99%